2009
DOI: 10.1037/a0016127
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ability for STEM domains: Aligning over 50 years of cumulative psychological knowledge solidifies its importance.

Abstract: The importance of spatial ability in educational pursuits and the world of work was examined, with particular attention devoted to STEM (science, technology, engineering, and mathematics) domains. Participants were drawn from a stratified random sample of U.S. high schools (Grades 9 -12, N ϭ 400,000) and were tracked for 11ϩ years; their longitudinal findings were aligned with pre-1957 findings and with contemporary data from the Graduate Record Examination and the Study of Mathematically Precocious Youth. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,149
1
42

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,489 publications
(1,227 citation statements)
references
References 73 publications
35
1,149
1
42
Order By: Relevance
“…After all, as exemplified in the work of Wai et al (2009), the link between spatial reasoning and STEM-related careers has been well established. On the other hand, however, there would seem no reason to expect that professionals would be inclined to highlight such elements, given the unlikeliness that spatial reasoning skills would have been a significant or explicit part of their formal education.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After all, as exemplified in the work of Wai et al (2009), the link between spatial reasoning and STEM-related careers has been well established. On the other hand, however, there would seem no reason to expect that professionals would be inclined to highlight such elements, given the unlikeliness that spatial reasoning skills would have been a significant or explicit part of their formal education.…”
Section: Resultsmentioning
confidence: 99%
“…Wai et al (2009) noted that business is one discipline that high school students with lower spatial reasoning tend to choose. Individuals with poorly developed spatial reasoning skills might be less able to recognize others using these skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should aim to find out more about the development of this spatial ability and the ontogenesis of individual differences. Recent research has shown that individual differences in spatial skills are predictive of later careers in STEM disciplines (Shea et al 2001;Wai et al 2009). Therefore, it is of important practical relevance to learn more about individual differences in mental rotation abilities, their origins, and means to foster this spatial skill at a young age.…”
Section: Discussionmentioning
confidence: 99%